2004
DOI: 10.1111/j.1466-7657.2004.00225.x
|View full text |Cite
|
Sign up to set email alerts
|

Nursing the dying: essential elements in the care of terminally ill patients

Abstract: Although the number of interviewed nurses in our study was small, the results corroborated the findings of other studies on the subject.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 7 publications
0
31
0
2
Order By: Relevance
“…While accepting the reality of death is a prominent feature of the palliative care movement (Callahan, 2009), it has rarely been addressed in research. When it has, it is usually because researchers found that accepting the reality of death was hard for family, caregivers or healthcare professionals (de Araujo, da Silva, & Francisco, 2004) or as a suggestion that healthcare professionals should be more open about the reality of death (Csikai, 2006). Families' difficulties accepting the reality of death are important to bear this in mind as we are working with families of the dying.…”
Section: Resultsmentioning
confidence: 99%
“…While accepting the reality of death is a prominent feature of the palliative care movement (Callahan, 2009), it has rarely been addressed in research. When it has, it is usually because researchers found that accepting the reality of death was hard for family, caregivers or healthcare professionals (de Araujo, da Silva, & Francisco, 2004) or as a suggestion that healthcare professionals should be more open about the reality of death (Csikai, 2006). Families' difficulties accepting the reality of death are important to bear this in mind as we are working with families of the dying.…”
Section: Resultsmentioning
confidence: 99%
“…Many nurses described how critical incidents triggered reflections of their own experiences with illness or of a death of a loved one (Cohen & Sarter 1992). A study by deAraujo et al (2004) reports nurses responses are both 'deeply moving and suffering' with each particular case. A study by deAraujo et al (2004) reports nurses responses are both 'deeply moving and suffering' with each particular case.…”
Section: Embodiment Of Practicementioning
confidence: 99%
“…Family members' awareness of the fact that their loved one is coming to the end of life could be affected by information provided by healthcare professionals. 39,40 A study showed challenges facing families at the end of life including bearing witness, the experience of loss, and final communications between patient and family. 3 The earlier the family members are aware that their loved one's life is coming to an end, the more time and opportunities they have to prepare for the death.…”
Section: Discussionmentioning
confidence: 99%